Anti-rust paint composition

JP7644819B2Active Publication Date: 2025-03-12CHUGOKU MARINE PAINTS
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023531988
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-30
Filing Date
2022-06-28
Publication Date
2025-03-12
Estimated Expiration
2042-06-28

AI Technical Summary

Benefits of technology

【0008】 本開示によれば、耐水性および耐白錆性に優れる無機ジンク塗膜を形成可能な水系無機ジンク防錆塗料組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644819000001
    Figure 0007644819000001
  • Figure 0007644819000002
    Figure 0007644819000002
  • Figure 0007644819000003
    Figure 0007644819000003
Patent Text Reader

Abstract

A rust preventive coating composition which contains: silica nanoparticles (A1); at least one zinc-based powder (B) that is selected from among a zinc powder and a zinc alloy powder; an aqueous titanium chelate compound (C); and water.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an anti-rust coating composition. [Background technology]

[0002] Conventionally, in order to prevent rusting during the construction of large steel structures, a primary rust-preventive paint composition (hereinafter, "paint composition" will also be simply referred to as "paint") has been applied to the surface of steel materials. Known primary rust-preventive paints include organic primary rust-preventive paints such as wash primer, non-zinc epoxy primer, and epoxy zinc rich primer, and inorganic zinc primary rust-preventive paints containing a siloxane binder and zinc powder. Among these primary rust-preventive paints, inorganic zinc primary rust-preventive paints with excellent weldability are the most widely used.

[0003] However, inorganic zinc primary rust-preventive paints containing siloxane-based binders and zinc powder contain a large amount of volatile organic solvents. In recent years, many countries have been required to reduce environmental impact, and primary rust-preventive paints that emit no or almost no volatile organic solvents are desired. Therefore, methods of using water instead of volatile organic solvents (water-based paints) have been considered. Examples of such water-based inorganic zinc paint compositions (hereinafter also referred to as "water-based inorganic zinc rust-preventive paint compositions") are described in Patent Documents 1 to 3. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-053769 A [Patent Document 2] Special Publication No. 2014-515771 [Patent Document 3] International Publication No. 2017 / 129784 Summary of the Invention [Problem to be solved by the invention]

[0005] The present inventors have found that when an inorganic zinc coating film is formed on a steel material using a conventional aqueous inorganic zinc paint composition to impart water resistance (rust resistance) to the steel material, white rust tends to occur on the coating film itself. Thus, when using a conventional aqueous inorganic zinc anti-rust paint composition, it is difficult to form a coating film that is excellent in both water resistance and white rust resistance, and water resistance and white rust resistance are in a so-called trade-off relationship.

[0006] One problem to be solved by the present disclosure is to provide an aqueous inorganic zinc anti-rust paint composition capable of forming an inorganic zinc coating film excellent in water resistance and white rust resistance.

Means for Solving the Problems

[0007] The present inventors have found that the above problems can be solved by an anti-rust paint composition having the following composition. That is, the anti-rust paint composition of the present disclosure contains silica nanoparticles (A1), at least one zinc-based powder (B) selected from zinc powder and zinc alloy powder, an aqueous titanium chelate compound (C), and water.

Effects of the Invention

[0008] According to the present disclosure, it is possible to provide an aqueous inorganic zinc anti-rust paint composition capable of forming an inorganic zinc coating film excellent in water resistance and white rust resistance.

Modes for Carrying Out the Invention

[0009] In the present disclosure, the numerical range n1 to n2 means n1 or more and n2 or less. Here, n1 and n2 are arbitrary numbers satisfying n1 < n2.

[0010] Hereinafter, the anti-rust paint composition and the like of the present disclosure will be described in detail. [Anti-rust paint composition] The anti-rust paint composition of the present disclosure (hereinafter, also simply referred to as "composition") contains silica nanoparticles (A1), at least one zinc-based powder (B) selected from zinc powder and zinc alloy powder, an aqueous titanium chelate compound (C), and water.

[0011] <Binders such as silica nanoparticles (A1)> The composition of the present disclosure contains silica nanoparticles (A1). The silica nanoparticles (A1) can function as a binder for forming a coating film in the composition. By using the silica nanoparticles (A1), for example, the sacrificial anticorrosive effect of the zinc-based powder (B) in the rust-preventive coating film formed from the composition can be improved.

[0012] The silica nanoparticles (A1) are not particularly limited as long as their average particle diameter is nano-sized (1000 nm or less). The average particle diameter of the silica nanoparticles (A1) is preferably 2 to 500 nm, more preferably 4 to 400 nm, and further preferably 10 to 300 nm. In the present disclosure, the average particle diameter of the silica nanoparticles is a converted value from a specific surface area measured by the BET adsorption method (in accordance with JIS Z8830:2013), and is an average primary particle diameter. Specifically, the specific surface area of ​​the particles is measured by the BET adsorption method, and the average particle diameter (nm)=6,000 / (specific surface area (m 2 / g) x true density (g / cm 3 )) Calculate the average particle size based on the formula. Examples of the silica nanoparticles (A1) include amorphous aqueous silica nanoparticles. Aqueous silica nanoparticles are particles that can be dispersed in an aqueous medium made of a liquid whose main component is water, and are particles derived from an aqueous silica sol. The main component refers to a component whose content is more than 50% by mass. The composition can contain one or more types of silica nanoparticles (A1).

[0013] The composition preferably further contains at least one component (A2) selected from alkoxysilanes, hydrolyzates of alkoxysilanes, and hydrolyzed condensates of alkoxysilanes (hereinafter also referred to as "alkoxysilane-based component (A2)"). Examples of the hydrolyzed condensates include dimers and trimers, siloxane oligomers of tetramers or more, and siloxane polymers. The alkoxysilane-based component (A2) can function as a binder for forming a coating film in the composition.

[0014] Examples of the alkoxysilane-based component (A2) include tetraalkoxysilane, alkylalkoxysilane, phenylalkoxysilane, mercaptoalkylalkoxysilane, aminoalkylalkoxysilane, ureidoalkylalkoxysilane, thiocyanatoalkylalkoxysilane, carboxyalkylalkoxysilane, glycidyloxyalkylalkoxysilane, bis(trimethoxysilylpropyl)amine and bis(alkoxysilylalkyl)amine, their hydrolyzates, and their hydrolyzed condensates. The carbon number of the alkoxy group in the alkoxysilane is preferably 5 or less, more preferably 3 or less.

[0015] Examples of tetraalkoxysilanes include tetramethoxysilane, tetraethoxysilane, tetra n-propoxysilane, tetraisopropoxysilane, tetra n-butoxysilane, and tetraisobutoxysilane.

[0016] Examples of alkylalkoxysilanes include C1 to C 16 -Alkylalkoxysilane, more preferably C1-C 16 -Alkyltrialkoxysilanes include, preferably, methyltrimethoxysilane, methyltriethoxysilane, methyltri-n-propoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane (PTMO), n-propyltriethoxysilane (PTEO), isobutyltrimethoxysilane (IBTMO), isobutyltriethoxysilane (IBTEO), octyltrimethoxysilane (OCTMO) and octyltriethoxysilane (OCTEO).

[0017] Examples of phenylalkoxysilanes include phenyltrialkoxysilanes, and preferred examples include phenyltrimethoxysilane and phenyltriethoxysilane.

[0018] Mercaptoalkylalkoxysilanes include, for example, 3-mercaptopropyltrimethoxysilane (MTMO) and 3-mercaptopropyltriethoxysilane (MTEO).

[0019] Examples of aminoalkylalkoxysilanes include 3-aminopropyltrimethoxysilane (AMMO), 3-aminopropyltriethoxysilane (AMEO), N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (DAMO), N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N,N'-diaminoethyl-3-aminopropyltrimethoxysilane (TriAMO) and N,N'-diaminoethyl-3-aminopropyltriethoxysilane.

[0020] Ureidoalkylalkoxysilanes include, for example, 3-ureidopropyltrimethoxysilane and 3-ureidopropyltriethoxysilane.

[0021] Thiocyanatoalkylalkoxysilanes include, for example, 3-thiocyanatopropyltrimethoxysilane and 3-thiocyanatopropyltrimethoxysilane.

[0022] Carboxyalkylalkoxysilanes include, for example, 3-carboxypropyltrimethoxysilane and 3-carboxypropyltriethoxysilane.

[0023] Glycidyloxyalkylalkoxysilanes include, for example, 3-glycidyloxypropyltrimethoxysilane and 3-glycidyloxypropyltriethoxysilane.

[0024] Bis(alkoxysilylalkyl)amines include, for example, bis(trimethoxysilylpropyl)amine and bis(triethoxysilylpropyl)amine. The composition may contain one or more alkoxysilane-based components (A2).

[0025] The composition may contain at least one selected from a crosslinking agent, a curing catalyst, and an additive in order to make the film-forming property of the silica nanoparticles (A1) uniform. Examples of the crosslinking agent include propyl zirconate, butyl titanate, and titanium acetylacetonate. One or more crosslinking agents may be used. Examples of the curing catalyst include organic acids such as formic acid, acetic acid, propionic acid, and maleic acid; inorganic acids such as hydrochloric acid, nitric acid, sulfuric acid, and phosphoric acid; caustic soda, caustic potash, N,N-dimethylethanolamine, and tetrakis(triethanolamine)zirconate. One or more curing catalysts may be used. Details of the additives will be described later.

[0026] The composition preferably contains an inorganic / organic hybrid binder that contains silica nanoparticles (A1) and an alkoxysilane-based component (A2) and further contains a crosslinking agent and / or a curing catalyst.

[0027] When preparing the above composition, an aqueous binder containing a binder containing silica nanoparticles (A1) and, if necessary, an alkoxysilane-based component (A2), and water can be used. As such an aqueous binder, commercially available products include, for example, "Dynasylan SIVO series" (manufactured by Evonik Japan Co., Ltd.), which contains silica nanoparticles (A1), an alkoxysilane-based component (A2), and water. In addition, an aqueous silica sol "Snowtex series" (manufactured by Nissan Chemical Co., Ltd.), which contains silica nanoparticles (A1) and water, can be mentioned. In particular, an inorganic / organic hybrid water-based binder containing silica nanoparticles (A1), an alkoxysilane component (A2), water, and a crosslinking agent and / or a curing catalyst, such as "Dynasylan SIVO 140" (SiO2 content: 14.25% by mass, solids concentration: 22.5% by mass, pH 3.8), is preferred, since it can be cured at room temperature, can form an anti-rust coating film with a thickness on the order of microns or more, and exhibits excellent performance.

[0028] The aqueous binder may be prepared by adding another aqueous silica sol to a commercially available inorganic / organic hybrid aqueous binder (e.g., Dynasylan SIVO 140). In this way, by relatively increasing the SiO2 content in the solid content of the aqueous binder, the zinc-based powder (B) can effectively exert a sacrificial anticorrosive effect, and the rust prevention of the single film when overcoated with a heavy-duty anticorrosive paint or the like can be improved. As the inorganic / organic hybrid aqueous binder, an acidic, neutral or alkaline aqueous binder can be used, but an acidic aqueous binder is preferred. As the acidic inorganic / organic hybrid aqueous binder, a pH of 2 to 6 is preferred, and a pH of 3 to 5 is particularly preferred. In the present disclosure, the pH is measured at 20°C using a pH meter.

[0029] The aqueous silica sol that may be added to the inorganic / organic hybrid aqueous binder may be acidic, neutral or alkaline, but when the inorganic / organic hybrid aqueous binder is acidic (e.g., "Dynasylan SIVO 140"), the aqueous silica sol added as required is preferably an acidic silica sol from the viewpoint of storage stability after mixing. The acidic silica sol preferably has a pH of 2 to 6, and more preferably has a pH of 3 to 5.

[0030] The aqueous silica sol added as required may contain at least one oxide selected from another sol-gel forming aqueous element oxide, such as aluminum oxide, silicon / aluminum oxide, titanium oxide, zirconium oxide and zinc oxide, together with the amorphous aqueous silica nanoparticles, and among these, it is preferable to contain silicon / aluminum oxide. The average particle size of the silica nanoparticles contained in the aqueous silica sol added as required is preferably 2 to 500 nm, more preferably 4 to 400 nm, even more preferably 10 to 200 nm, and particularly preferably 17 to 150 nm. An aqueous silica sol containing silica nanoparticles having an average particle size of 17 nm or more and 150 nm or less and an aqueous silica sol containing silica nanoparticles having an average particle size of 2 nm or more and less than 17 nm may be used in combination. The stability of the composition is improved by the silica nanoparticles having an average particle size of 17 nm or more and 150 nm or less, and the viscosity of the composition is moderately increased by the silica nanoparticles having an average particle size of 2 nm or more and less than 17 nm, and the anti-settling property can be improved.

[0031] Examples of commercially available aqueous silica sols include "Snowtex O", "Snowtex OL", and "Snowtex OYL", which are acidic silica sols having an anionic surface of dispersoid, and "Snowtex AK", "Snowtex AK-L", and "Snowtex AK-YL", which are acidic silica sols having a cationic surface of dispersoid (all manufactured by Nissan Chemical Industries, Ltd.). From the viewpoint of storage stability of the composition, cationic acidic silica sols are preferred.

[0032] The SiO2 content in the solid content of the composition or in the anticorrosive coating film formed from the composition is preferably 0.5 to 30% by mass, more preferably 1 to 20% by mass, and even more preferably 2 to 15% by mass. The SiO2 content in the above range is preferable in terms of anticorrosive properties. The SiO2 content in the solid content of the composition and the SiO2 content in the anticorrosive coating film refer to the total content of the SiO2 component derived from the silica nanoparticles (A1) and the SiO2 component derived from the alkoxysilane-based component (A2). The SiO2 component derived from the silica nanoparticles (A1) includes the SiO2 component derived from the aqueous silica sol added as necessary. The amount of the SiO2 component can be measured by the method described in International Publication No. WO 2012 / 130544.

[0033] The solid content of the composition refers to the components remaining as a coating film when the composition is cured, excluding volatile components such as water and organic solvents from the composition.

[0034] The content mass ratio of the silica nanoparticles (A1) to the alkoxysilane-based component (A2) in the above composition (silica nanoparticles (A1) / alkoxysilane-based component (A2)) is preferably 0.1 to 12.0, more preferably 0.5 to 8.0. The silica nanoparticles (A1) include silica nanoparticles contained in an aqueous silica sol that is added as needed.

[0035] <Zinc-based powder (B)> The zinc-based powder (B) is at least one selected from zinc powder and zinc alloy powder. The zinc-based powder (B) acts as an anti-rust pigment that prevents rusting of steel materials.

[0036] The zinc alloy powder may be, for example, a powder of an alloy of zinc and at least one selected from aluminum, magnesium, and tin, preferably a zinc-aluminum alloy or a zinc-tin alloy.

[0037] The shape of the particles constituting the zinc-based powder (B) may be various, such as spherical or scaly. Commercially available zinc powders having a spherical particle shape include, for example, "F-2000" (manufactured by Honjo Chemical Co., Ltd.). Commercially available zinc powders having a scaly particle shape include, for example, "STANDART Zinc flake GTT" and "STANDART Zinc flake G" (manufactured by ECKART GmbH). Commercially available zinc alloy powders having a scaly particle shape include, for example, "STAPA 4 ZNAL7" which is an alloy of zinc and aluminum, and "STAPA 4 ZNSN30" which is an alloy of zinc and tin (manufactured by ECKART GmbH).

[0038] As the zinc-based powder (B), one or both of zinc powder and zinc alloy powder can be used, and one or more of the zinc powder and zinc alloy powder may be used.

[0039] The composition may contain one or more zinc-based powders (B). The content of the zinc-based powder (B) in the solid content of the above composition or in the anti-rust coating film formed from the above composition is preferably 80 mass % or less, more preferably 40 to 70 mass %, and even more preferably 45 to 60 mass %.

[0040] <Water-based titanium chelate compound (C)> The composition of the present disclosure contains a water-based titanium chelate compound (C). The water-based titanium chelate compound refers to a titanium chelate compound that can be mixed or dissolved in water without causing gelation, precipitation, cloudiness, etc., when added to water so that the content of the compound is 1% by mass at a temperature of 25° C. It is preferable that the water-based titanium chelate compound can be mixed or dissolved in water in an amount of 30% by mass at a temperature of 25° C., without causing gelation, precipitation, cloudiness, etc.

[0041] In the prior art, as described above, water resistance and white rust resistance are in a so-called trade-off relationship, and it is generally believed that improving water resistance will result in a decrease in white rust resistance. White rust is a component (e.g., a mixture of zinc oxide, zinc hydroxide, zinc carbonate, etc.) that may occur on the surface of a coating film when a steel material coated with an inorganic zinc paint composition is exposed outdoors, as the zinc powder in the coating film reacts with water, oxygen, or carbon dioxide. By forming an anti-rust coating film on a steel material using an anti-rust coating composition containing silica nanoparticles (A1) and a zinc-based powder (B) together with a water-based titanium chelate compound (C), it is possible to impart excellent water resistance (red rust resistance) to the steel material and suppress the occurrence of white rust in the anti-rust coating film, although the reason is unclear. Therefore, the effect of the present disclosure, which can achieve both water resistance and white rust resistance, can be said to be an advantageous effect.

[0042] In addition, when white rust occurs in the primary rust-preventive coating film, the formability or adhesion of the topcoat coating film on the primary rust-preventive coating film may decrease. Therefore, in this case, a step of removing the white rust on the coating film surface may be required. The rust-preventive coating composition of the present disclosure can suppress the occurrence of white rust in the rust-preventive coating film, and therefore can also improve the formability or adhesion of the topcoat coating film on the primary rust-preventive coating film.

[0043] Examples of the water-based titanium chelate compound (C) include organic titanium compounds represented by the formula Ti(X)4 and their oligomers. Each X is independently a hydroxy group, an alkoxy group, or a chelating substituent, provided that at least one X is a chelating substituent. At least one X is preferably a hydroxy group or an alkoxy group. For example, it is preferred that two Xs are hydroxy groups or alkoxy groups, and two Xs are chelating substituents.

[0044] Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group such as an n-propoxy group and an isopropoxy group, and a butoxy group such as an n-butoxy group, an isobutoxy group and a tert-butoxy group. The number of carbon atoms in the alkoxy group is preferably 6 or less, more preferably 4 or less.

[0045] The chelating substituent is a group derived from an organic compound capable of forming a chelate. Examples of the organic compound capable of forming a chelate include alkanolamines, hydroxycarboxylic acids, and salts of hydroxycarboxylic acids. The chelating substituent is, for example, a ligand derived from an alkanolamine, a ligand derived from a hydroxycarboxylic acid, or a ligand derived from a salt of a hydroxycarboxylic acid.

[0046] Among the water-based titanium chelate compounds (C), the use of the above-mentioned organotitanium compounds having a ligand derived from an alkanolamine as a chelating substituent can form an anti-rust coating film with even better white rust resistance, although the reason is unclear. Among the water-based titanium chelate compounds (C), the use of the above-mentioned organotitanium compounds having a ligand derived from a salt of a hydroxycarboxylic acid as a chelating substituent can form an anti-rust coating film with even better salt spray corrosion resistance, although the reason is unclear.

[0047] Alkanolamine is an amine compound having a hydroxy group on an alkane skeleton. Examples of alkanolamine include alkanolamines having 12 or less carbon atoms, preferably 4 to 12 carbon atoms, more preferably 6 to 12 carbon atoms. Specific examples of alkanolamine include triethanolamine, diethanolamine, monoethanolamine, N-methyldiethanolamine, N-methyldiisopropanolamine, triisopropanolamine, and 2-(2-aminoethylamino)ethanol, and triethanolamine is preferred.

[0048] Hydroxycarboxylic acid is a compound having a carboxy group and a hydroxy group. Examples of hydroxycarboxylic acid include hydroxycarboxylic acid having 7 or less carbon atoms, preferably 2 to 4 carbon atoms. Specific examples of hydroxycarboxylic acid include glycolic acid, lactic acid, hydroxybutyric acid, glyceric acid, malic acid, and tartaric acid, and lactic acid is preferred. Examples of salts of hydroxycarboxylic acid include ammonium salts of hydroxycarboxylic acid, and ammonium lactate is preferred.

[0049] Specific examples of the chelating substituent include ligands derived from triethanolamine, diethanolamine, lactic acid, or ammonium lactate. From the viewpoint of further improving white rust resistance, ligands derived from triethanolamine or diethanolamine are preferred, and from the viewpoint of improving salt spray corrosion resistance, ligands derived from ammonium lactate are preferred.

[0050] Examples of the aqueous titanium chelate compound (C) include: Titanium lactates such as dihydroxytitanium bis(lactate); ammonium titanium lactates such as dihydroxytitanium bis(ammonium lactate) and dipropoxytitanium bis(ammonium lactate); Titanium triethanolamines such as dipropoxytitanium bis(triethanolamine), diisopropoxytitanium bis(triethanolamine), dibutoxytitanium bis(triethanolamine) and propoxytitanium(triethanolamine); titanium diethanolamines such as dipropoxytitanium bis(diethanolamine) and dibutoxytitanium bis(diethanolamine); titanium aminoethylaminoethanolates such as (C3H7O)Ti(OC2H4NHC2H4NH2)3; Hydrolyzates of the titanium chelates exemplified above; and Titanium oligomers obtained by hydrolysis and condensation of the titanium chelates exemplified above; Examples include:

[0051] The above composition may contain one or more water-based titanium chelate compounds (C).

[0052] The content of the water-based titanium chelate compound (C) is preferably 0.1 to 4.5 parts by mass, more preferably 0.2 to 3.0 parts by mass, and even more preferably 0.3 to 2.0 parts by mass, based on 100 parts by mass of the zinc-based powder (B) in terms of TiO2. By making the content of the water-based titanium chelate compound (C) below the upper limit, for example, the increase in viscosity in the coating composition can be suppressed, and therefore a coating composition with excellent coating properties can be obtained. In addition, by making the content of the water-based titanium chelate compound (C) below the upper limit, excellent effects can be obtained in terms of white rust resistance and water resistance.

[0053] The content of the water-based titanium chelate compound (C) is preferably 1 to 45 parts by mass, more preferably 5 to 45 parts by mass, and even more preferably 10 to 45 parts by mass, based on 100 parts by mass of the binder components excluding SiO2, calculated as TiO2. By making the content of the water-based titanium chelate compound (C) equal to or less than the upper limit, for example, it is possible to form an anti-rust coating film with even better water resistance. The binder components excluding SiO2 include, for example, the components of the alkoxysilane component (A2) other than the components capable of forming SiO2, the above-mentioned crosslinking agent, and the curing catalyst.

[0054] <Aluminum phosphate component (D)> The composition of the present disclosure may further contain an aluminum phosphate-based component (D). The aluminum phosphate-based component (D) not only acts as an anti-rust pigment that prevents rusting of steel materials, but is also effective in improving salt spray corrosion resistance. Examples of the aluminum phosphate-based component (D) include aluminum phosphate-based compounds and aluminum phosphate-based pigments obtained by treating aluminum phosphate-based compounds with a treating agent.

[0055] Examples of aluminum phosphate compounds include aluminum pyrophosphate, aluminum dihydrogen triphosphate, aluminum metaphosphate, aluminum orthophosphate, and aluminum phosphite. Among these, condensed aluminum phosphates such as aluminum pyrophosphate, aluminum dihydrogen triphosphate, and aluminum metaphosphate are preferred, and aluminum dihydrogen tripolyphosphate is more preferred.

[0056] Examples of the treatment include surface treatment, modification treatment, and mixing treatment. Aluminum phosphate pigments obtained by treating condensed aluminum phosphate such as aluminum pyrophosphate, aluminum dihydrogen triphosphate, and aluminum metaphosphate are preferred.

[0057] The above treatment can be carried out, for example, to adjust the pH of the aluminum phosphate compound or to adjust the amount of phosphate ions eluted. Examples of the treatment agent used in the above treatment include conductive pigments (E) or pigments (F) described below, which contain at least one selected from Si, Zn, Mg, and Ca, and molybdic acid.

[0058] As the aluminum phosphate-based pigment, a pigment obtained by treating condensed aluminum phosphate as described above is preferred, and a pigment obtained by treating aluminum dihydrogen triphosphate as described above is more preferred. From the viewpoint of corrosion prevention, a pigment obtained by treating condensed aluminum phosphate with molybdic acid is more preferred, and a pigment obtained by treating aluminum dihydrogen tripolyphosphate with molybdic acid is even more preferred.

[0059] Commercially available aluminum phosphate pigments include, for example, "K-WHITE #84" (manufactured by Teika Corporation), which is obtained by surface-treating aluminum dihydrogen triphosphate with a treatment agent containing Si and Zn, "K-WHITE CZ610" (manufactured by Teika Corporation), which is obtained by surface-treating aluminum dihydrogen triphosphate with a treatment agent containing Ca and Zn, "K-WHITE G105" (manufactured by Teika Corporation), which is obtained by surface-treating aluminum dihydrogen triphosphate with a treatment agent containing magnesium, and "LF BOSEI PM-303W" (manufactured by Kikuchi Color Co., Ltd.), which is obtained by modifying aluminum dihydrogen triphosphate with a treatment agent containing molybdic acid.

[0060] The composition may contain one or more aluminum phosphate-based components (D).

[0061] When an aluminum phosphate-based component (D) is used, the content of the aluminum phosphate-based component (D) in the solid content of the composition or in the rust-preventive coating film formed from the composition is preferably 0.5 to 70 mass%, more preferably 1 to 50 mass%, and even more preferably 2 to 40 mass%. When the content of the aluminum phosphate-based component (D) is within the above range, for example, an anti-rust coating film with even more excellent rust prevention properties can be formed.

[0062] <Conductive pigment (E)> The composition of the present disclosure may further contain a conductive pigment (E). By using the conductive pigment (E) in combination with, for example, a zinc-based powder (B) and an aluminum phosphate-based component (D), the sacrificial anticorrosive action of the zinc-based powder (B) can be improved, and thus the rust prevention properties can be improved.

[0063] Examples of the conductive pigment (E) include zinc oxide, zinc-based powder (B), metal powder or metal alloy powder other than molybdenum and molybdenum compounds described below, and carbon powder. Among these, zinc oxide is preferred from the viewpoints of low cost and high conductivity.

[0064] Commercially available zinc oxide products include, for example, "Zinc Oxide Type 1" (manufactured by Sakai Chemical Industry Co., Ltd.) and "Zinc Oxide Type 3" (manufactured by Hakusui Tech Co., Ltd.).

[0065] Examples of metal powders or metal alloy powders other than the zinc-based powder (B) include Fe-Si powder, Fe-Mn powder, Fe-Cr powder, magnetic iron powder, and iron phosphide. Examples of commercially available metal powders or metal alloy powders include "Ferrosilicon" (Kinsei Matec Co., Ltd.), "Ferromanganese" (Kinsei Matec Co., Ltd.), "Ferrochrome" (Kinsei Matec Co., Ltd.), "Iron Sand Powder" (Kinsei Matec Co., Ltd.), and "Ferrophos 2132" (Occidental Chemical Corporation).

[0066] An example of the carbon powder is carbon black, which is used as a color pigment. An example of a commercially available carbon powder is "Mitsubishi Carbon Black MA-100" (manufactured by Mitsubishi Chemical Corporation).

[0067] The composition may contain one or more types of conductive pigments (E). When the conductive pigment (E) is used, the content of the conductive pigment (E) in the solid content of the composition or in the rust-preventive coating film formed from the composition is preferably 0.1 to 50 mass%, more preferably 1 to 40 mass%, and even more preferably 2 to 30 mass%. When the content of the conductive pigment (E) in the composition is within the above range, for example, a coating film having even more excellent rust prevention properties can be formed.

[0068] <Pigment (F)> The composition of the present disclosure may further contain a pigment (F). The pigment (F) is a pigment other than the above-mentioned (B), (D), and (E), and examples thereof include extender pigments, color pigments, and anti-rust pigments other than the above-mentioned (B), (D), and (E).

[0069] The composition may contain one or more pigments (F). When pigment (F) is used, the content of pigment (F) in the solid content of the composition or in the anti-rust coating film formed from the composition is preferably 1 to 60 mass%, more preferably 2 to 50 mass%, and even more preferably 3 to 40 mass%.

[0070] The extender pigment is not particularly limited as long as it is an inorganic pigment used in general paints, and examples thereof include potassium feldspar, soda feldspar, kaolin, mica, silica, glass powder, talc, barium sulfate, aluminum oxide, zirconium silicate, wollastonite, and diatomaceous earth. The extender pigment may be an inorganic pigment that generates a gas by thermal decomposition. As the extender pigment, potassium feldspar, kaolin, silica, and glass powder are preferred. When kaolin is used, its content in the solid content of the composition or in the rust-preventive coating film formed from the composition is preferably 0.1 to 60 mass%, more preferably 1 to 40 mass%, and even more preferably 5 to 35 mass%. As the silica classified as an extender pigment, silica particles having an average particle size of preferably more than 1 μm and not more than 10 μm can be used. The average particle size of such silica particles can be measured by a particle size distribution measuring device using a laser diffraction method.

[0071] Commercially available extender pigments include, for example, the potassium feldspar "Ceramics Powder OF-T" (manufactured by Kinsei Matec Co., Ltd.), "Mica Powder 100 Mesh" (manufactured by Fukuoka Talc Kogyosho Co., Ltd.), the kaolin "Satintone W" (manufactured by BASF), the zirconium silicate "A-PAX45M" (manufactured by Kinsei Matec Co., Ltd.), "FC-1 Talc" (manufactured by Fukuoka Talc Kogyosho Co., Ltd.), "Silica QZ-SW" (manufactured by Goto Mines Co., Ltd.), "Precipitated Barium Sulfate 100" (manufactured by Sakai Chemical Industry Co., Ltd.), and the diatomaceous earth "Radiolite" (manufactured by Showa Chemical Industry Co., Ltd.). The composition may contain one or more extender pigments.

[0072] Glass powder is generally prepared by heating and melting a compound constituting glass at about 1,000 to 1,100°C for a predetermined time, cooling, and then granulating the compound into a powder using a grinding device. Examples of compounds constituting glass include SiO2, B2O3, Al2O3, ZnO, BaO, MgO, CaO, SrO, Bi2O3, Li2O, Na2O, K2O, PbO, P2O5, In2O3, SnO, CuO, Ag2O, V2O5, and TeO2. PbO can also be used as a compound constituting glass, but it is preferable not to use PbO because it may have a negative effect on the environment.

[0073] A glass powder having a softening point of 400 to 800° C. is preferred because it acts as an antioxidant for the zinc-based powder (B) when the rust-preventive coating film made of the above composition is heated at a high temperature of 400 to 900° C. The softening point of the glass powder is determined by a method using a Littleton viscometer and determining the temperature at which the viscosity coefficient η reaches the power of 107.6.

[0074] Commercially available glass powders include, for example, "NB122A" (softening point 400° C.), "AZ739" (softening point 605° C.), and "PFL20" (softening point 700° C.) (manufactured by Central Glass Co., Ltd.).

[0075] B2O3, one of the compounds that make up glass, is a glass-like substance with a softening point of about 450°C by itself and can be used as glass powder. An example of a commercially available product of B2O3 is "boron oxide" (Kanto Chemical Co., Ltd., Shika Grade 1 Reagent).

[0076] The composition may contain one or more glass powders. When glass powder is used, the content of the glass powder in the solid content of the composition or in the anti-rust coating film formed from the composition is preferably 0.05 to 26 mass %, more preferably 0.15 to 20 mass %, and even more preferably 0.5 to 15 mass %.

[0077] The inorganic pigment that generates gas by thermal decomposition is, for example, an inorganic pigment that generates gas such as CO2 and F2 by thermal decomposition at 500 to 1,500 ° C. Examples of the inorganic pigment that generates gas by thermal decomposition include calcium carbonate, magnesium carbonate, strontium carbonate, and calcium fluoride. When the composition contains such an inorganic pigment, when welding a substrate covered with the coating film, the coating film-forming solid content of the binder containing silica nanoparticles (A1) and the gas derived from the components (B), (D), (E) and (F) in the molten pool at the time of welding can be removed from the molten pool together with the gas derived from the inorganic pigment.

[0078] Commercially available inorganic pigments that generate gas upon thermal decomposition include, for example, "Fluorite 400 Mesh" (Kinsei Matec Co., Ltd.), "NS#400" (Nitto Funka Kogyo Co., Ltd.), "Magnesium Carbonate" (Tomita Pharmaceutical Co., Ltd.), and "Strontium Carbonate A" (Honjo Chemical Co., Ltd.). The composition may contain one or more of the inorganic pigments described above.

[0079] The color pigment other than the above-mentioned (B), (D) and (E) is at least one selected from inorganic color pigments and organic color pigments. The inorganic color pigment is not particularly limited as long as it is an inorganic color pigment other than the conductive pigment (E), and examples thereof include metal oxides such as titanium oxide and iron oxide; copper-chromium-manganese, iron-manganese, iron-chromium, cobalt-titanium-nickel-zinc, and cobalt-chromium-titanium-zinc composite oxides. Examples of the organic color pigment include organic color pigments such as phthalocyanine green and phthalocyanine blue.

[0080] Commercially available color pigments include, for example, "TITONE R-5N" (manufactured by Sakai Chemical Industry Co., Ltd.), "Red Iron Ore No. 404" (manufactured by Morishita Red Iron Ore Industry Co., Ltd.), "Dipyroxide Black #9510" (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.), "Heliogen Green L8690" (manufactured by BASF Japan Ltd.), and "FASTOGEN Blue 5485" (manufactured by DIC Corporation). The composition may contain one or more color pigments.

[0081] Examples of anti-rust pigments other than the above-mentioned (B), (D) and (E) include molybdenum and molybdenum compounds, zinc phosphate compounds, calcium phosphate compounds, magnesium phosphate compounds, zinc phosphite compounds, calcium phosphite compounds, strontium phosphite compounds, zinc cyanamide compounds and borate compounds.

[0082] Molybdenum (metallic molybdenum) and molybdenum compounds act as antioxidants (so-called white rust inhibitors) for the zinc-based powder (B), which reduces the occurrence of the above-mentioned white rust in the anticorrosive coating film formed. The above composition may contain one or both of molybdenum and molybdenum compounds.

[0083] Examples of the molybdenum compound include molybdenum oxides such as molybdenum trioxide, molybdenum sulfide, molybdenum halides, metal salts of molybdic acid such as molybdic acid, ammonium molybdate, phosphomolybdic acid, silicomolybdic acid, and zinc molybdate, alkali metal salts of molybdic acid, alkali metal salts of phosphomolybdic acid, alkali metal salts of silicomolybdic acid, alkaline earth metal salts of molybdic acid such as calcium molybdate, alkaline earth metal salts of phosphomolybdic acid, alkaline earth metal salts of silicomolybdic acid, manganese salts of molybdic acid, manganese salts of phosphomolybdic acid, manganese salts of silicomolybdic acid, basic nitrogen-containing compound salts of molybdic acid, basic nitrogen-containing compound salts of phosphomolybdic acid, and basic nitrogen-containing compound salts of silicomolybdic acid.

[0084] The composition can contain one or more molybdenum compounds. When one or both of molybdenum and a molybdenum compound are used, the total content of molybdenum and the molybdenum compound is preferably 0.05 to 5.0 parts by mass, more preferably 0.3 to 3.0 parts by mass, and even more preferably 0.5 to 2.0 parts by mass, based on 100 parts by mass of zinc-based powder (B). When the content is within the above range, a sufficient antioxidant effect of zinc-based powder (B) can be obtained, and the activity of zinc-based powder (B) can be prevented from decreasing, and the anticorrosive properties of the coating film can be maintained. The composition may contain one or more of the above anti-rust pigments.

[0085] <Other ingredients> The composition of the present disclosure may contain, as other components, additives and the like, as appropriate, within a range that does not impair the objects and effects of the present disclosure.

[0086] Examples of additives include thixotropic agents, defoamers, wetting agents, surface conditioners, suspending agents, anti-sagging agents, drying agents, flowability conditioners, dispersants, color separation inhibitors, anti-skinning agents, plasticizers, and ultraviolet absorbers.Specific paint additives include polycarboxylic acid-based thixotropic agents, fatty acid polyamide-based thixotropic agents, polyethylene oxide-based thixotropic agents, urethane association-based thixotropic agents, acrylic polymer-based thixotropic agents, and modified urea-based thixotropic agents; modified silicone-based defoamers and polymer-based defoamers; modified silicone-based surface conditioners, acrylic polymer-based surface conditioners, fluorine-containing polymer-based surface conditioners, and dialkylsulfosuccinate-based surface conditioners; and clay-based suspending agents such as hectorite, bentonite, and smectite. The composition may contain one or more additives.

[0087] <Water> The composition of the present disclosure contains water to dissolve or disperse binders such as silica nanoparticles (A1) and alkoxysilane-based components (A2). Here, the water may be the water used when producing the first agent described below, or may be the water added during the preparation process of mixing the above-mentioned aqueous binder, zinc-based powder (B), aqueous titanium chelate compound (C), aluminum phosphate-based component (D), conductive pigment (E), pigment (F), and other components described above.

[0088] Water is contained in the composition and functions as a solvent or dispersion medium for binders such as silica nanoparticles (A1) and alkoxysilane-based components (A2), and has the function of stably holding the binder in the composition. Therefore, the viscosity of the aqueous coating composition can be kept appropriate, and the workability of sprays, brushes, rollers, etc. can be maintained well. From this viewpoint, the content of water in the composition is preferably 10 to 90% by mass, more preferably 20 to 80% by mass, and even more preferably 30 to 70% by mass.

[0089] <Hydrophilic organic solvent> The composition of the present disclosure may further contain a hydrophilic organic solvent. Examples of hydrophilic organic solvents include acetone, methyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, 2-butoxyethanol, 2-ethoxyethanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, ethyl alcohol, 2-methoxyethanol, diacetone alcohol, dioxane, ethylene glycol, ethylene glycol diethyl ether, ethylene glycol dimethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, and ethylene glycol monohexyl ether.

[0090] The composition may contain one or more hydrophilic organic solvents. When the composition contains a hydrophilic organic solvent, it is preferable in that the solubility and dispersibility of the above (B) to (F) in water is improved, the wettability of the composition to the substrate (substrate) is improved, and the drying and curing properties of the coating film are improved. However, when the amount of the hydrophilic organic solvent added is large, although the solubility and dispersibility of the above (B) to (F) in water is improved, it is not preferable from the viewpoint of environmental regulations for reducing volatile organic compounds (VOCs). From this viewpoint, the content of the hydrophilic organic solvent in the composition is preferably less than 15% by mass, more preferably less than 10% by mass, and even more preferably less than 5% by mass. The content of organic solvents including the hydrophilic organic solvent in the composition is also preferably less than 15% by mass, more preferably less than 10% by mass, and even more preferably less than 5% by mass.

[0091] <Pigment volume concentration (PVC)> The composition of the present disclosure has a pigment volume concentration (PVC) of preferably 70% or more, more preferably 70 to 90%, and even more preferably 75 to 85%. In the present disclosure, the pigment volume concentration (PVC) refers to the concentration expressed as a percentage of the ratio (by volume) of the pigment component and solid particles in the additives to the solid content of the composition. PVC = [total volume of all pigment components + total volume of solid particles in additives] / [volume of solid content of coating composition] x 100 (%)

[0092] The "pigment components" include zinc-based powder (B), aluminum phosphate-based component (D), conductive pigment (E), and pigment (F). The solid components of the coating composition other than the pigment components include silica nanoparticles (A1), alkoxysilane-based component (A2), and water-based titanium chelate compound (C), as well as solid particles in the additives.

[0093] In calculating the PVC, the volume of each component is calculated from the mass of each component and its true density (hereinafter simply referred to as "density").

[0094] The volume of the solid content (non-volatile content) of the composition can be calculated from the mass and density of the solid content of the composition. The mass and density may be measured values, or if it is difficult to measure them, they may be values ​​calculated from the raw materials used.

[0095] The volume of the pigment component can be calculated from the mass and density of the pigment component used. The mass and density may be measured values, or may be values ​​calculated from the raw materials used if measurement is difficult. For example, the volume can be calculated by separating the pigment component from other components from the non-volatile content of the composition and measuring the mass and density of the separated pigment component. The same applies to solid particles in the additive.

[0096] <Uses of anti-rust paint composition> The composition of the present disclosure can be preferably used as a primary anti-rust paint composition in painting steel materials for large structures. Examples of large structures include ships, marine structures, plants, bridges, and land tanks. The primary anti-rust paint composition is required to protect steel materials from rust during the construction period without interfering with melting and welding during the construction process of the large structures.

[0097] For example, the primary rust-preventive coating composition is applied to a substrate such as a steel material to form a primary rust-preventive coating film. The substrate to be coated is then subjected to a blast treatment under conditions equivalent to a rust removal degree Sa2 1 / 2 or more in ISO 8501-1.

[0098] On the surface of the rust-preventive coating film formed from the above composition, a topcoat coating film can be formed by applying a paint such as an epoxy resin-based, chlorinated rubber-based, oil-based, epoxy ester-based, polyurethane resin-based, polysiloxane resin-based, fluororesin-based, acrylic resin-based, vinyl resin-based, or inorganic zinc-based paint. The above rust-preventive coating film also has excellent adhesion to the topcoat coating film.

[0099] [Anti-rust paint composition kit] The anticorrosive paint composition kit (hereinafter, simply referred to as "kit") of the present disclosure has a first agent and a second agent. The first agent contains silica nanoparticles (A1), a water-based titanium chelate compound (C) and water, and preferably further contains an alkoxysilane-based component (A2). The second agent contains a zinc-based powder (B).

[0100] The first agent contains the water-based titanium chelate compound (C), and the storage stability is greatly improved, although the reason is unclear. Here, the storage stability can be judged, for example, by comparing the water resistance of the rust-preventive coating film formed from the coating composition obtained by mixing the first agent with the second agent several days after preparation with the water resistance of the rust-preventive coating film formed from the coating composition obtained by mixing the first agent with the second agent after storing for two months. That is, the first agent containing the water-based titanium chelate compound (C) in addition to the silica nanoparticles (A1), the alkoxysilane component (A2) if necessary, and water can form a rust-preventive coating film with excellent water resistance even after a certain period of storage.

[0101] At least one selected from the first agent and the second agent, for example the second agent, preferably further contains an aluminum phosphate-based component (D).At least one selected from the first agent and the second agent, for example the second agent, preferably further contains a conductive pigment (E).

[0102] At least one selected from the first agent and the second agent, for example the second agent, preferably further contains a pigment (F). The second agent preferably contains a zinc-based powder (B), an aluminum phosphate-based component (D) and a conductive pigment (E), and more preferably further contains a pigment (F).

[0103] The first agent is, for example, an aqueous binder containing silica nanoparticles (A1), an alkoxysilane component (A2) if necessary, an aqueous titanium chelate compound (C), and water. The SiO2 content in the first agent (or the aqueous binder) is preferably 0.5 to 50 mass%, more preferably 1 to 30 mass%, and even more preferably 2 to 15 mass%. The SiO2 content in the solid content of the first agent is preferably 40 to 95 mass%, and more preferably 50 to 90 mass%.

[0104] From the viewpoint of preventing precipitation of the silica nanoparticles (A1) in the first agent during long-term storage, the average particle size of the silica nanoparticles contained in the aqueous silica sol is preferably 100 nm or less, and more preferably 50 nm or less.

[0105] The content of the water-based titanium chelate compound (C) in the first agent is preferably 0.1 to 1.5 mass %, more preferably 0.2 to 1.2 mass %, calculated as TiO2. With this constitution, the storage stability of the first agent can be further improved.

[0106] The content mass ratio of the silica nanoparticles (A1) to the alkoxysilane-based component (A2) in the first agent (silica nanoparticles (A1) / alkoxysilane-based component (A2)) is preferably 0.1 to 12.0, more preferably 0.5 to 8.0. The silica nanoparticles (A1) include silica nanoparticles contained in an aqueous silica sol that is added as needed.

[0107] The content of water in the first agent is preferably 30 to 98 mass %, more preferably 50 to 95 mass %, and even more preferably 70 to 92 mass %.

[0108] At least one selected from the first agent and the second agent may contain the other components described above.

[0109] The composition can be easily prepared by mixing the first and second agents constituting the kit. The content ratio of each component in the first and second agents can be appropriately set so that the content ratio of each component when the composition is prepared by mixing the first and second agents falls within the range described in the [Anti-rust paint composition] column.

[0110] [Anti-rust coating film, primary anti-rust coating film, anti-rust substrate and method for producing same] The rust-preventive substrate of the present disclosure has a substrate and a rust-preventive coating film and / or a primary rust-preventive coating film formed on the substrate, wherein the rust-preventive coating film and the primary rust-preventive coating film are formed from the composition of the present disclosure or the kit of the present disclosure.

[0111] The average dry film thickness of the antirust coating film and / or primary antirust coating film formed from the above composition or kit, as measured with an electromagnetic film thickness meter, is preferably 30 μm or less, more preferably 5 to 25 μm.

[0112] The method for producing a rust-preventing substrate of the present disclosure includes the steps of: [1] coating a substrate with a composition of the present disclosure; and [2] curing the composition coated on the substrate to form a rust-preventing coating film on the substrate.

[0113] Examples of the substrate include steels such as iron, steel, ferroalloy, carbon steel, mild steel, and alloy steel, and more specifically, the above-mentioned steel materials for large structures, etc. If necessary, the substrate is preferably blasted under conditions corresponding to a rust removal degree Sa2 1 / 2 or more in ISO 8501-1.

[0114] Examples of the method for applying the anti-rust coating composition to the substrate include coating the anti-rust coating composition on the substrate, or impregnating the substrate with the anti-rust coating composition and then removing the substrate. There are no particular limitations on the method for applying the anti-rust coating composition, and conventionally known methods such as air spray and airless spray can be used.

[0115] Airless sprayers and line coaters are generally used for painting at shipyards, steelworks, etc. Line coaters control the film thickness by painting conditions such as the line speed, the painting pressure of the air sprayer and airless sprayer installed inside the coater, and the size (diameter) of the spray tip.

[0116] For example, the composition is applied onto a substrate and then cured. There is no particular restriction on the curing method, and any conventionally known curing method can be applied. For example, when the composition applied onto a substrate is left in the air, the water in the composition and the hydrophilic organic solvent optionally contained therein volatilize and cure. At this time, the coating film may be heated and dried as necessary. Examples of the heating method include a method using a tunnel-type heating system using combustion gas, oil burner, electric heating wire heating, induction heating, and far-infrared heating equipment, a direct heating method using gas or oil burner, or a method using infrared radiation or an induction heating system.

[0117] The present disclosure relates to, for example, the following (1) to (16). (1) An anti-rust coating composition comprising silica nanoparticles (A1), at least one zinc-based powder (B) selected from zinc powder and zinc alloy powder, a water-based titanium chelate compound (C), and water. (2) The anticorrosive coating composition according to the above (1), wherein the aqueous titanium chelate compound (C) is at least one selected from organic titanium compounds represented by the formula Ti(X)4 (wherein X is each independently a hydroxyl group, an alkoxy group or a chelating substituent, provided that at least one X is a chelating substituent) and oligomers thereof. (3) The rust-preventive coating composition according to the above (2), wherein the aqueous titanium chelate compound (C) is an organic titanium compound in which the chelating substituent is a ligand derived from an alkanolamine, a ligand derived from a hydroxycarboxylic acid, or a ligand derived from a salt of a hydroxycarboxylic acid. (4) The rust-preventive coating composition according to (2) or (3) above, wherein the aqueous titanium chelate compound (C) is the above-mentioned organotitanium compound in which the chelating substituent is a ligand derived from an alkanolamine. (5) The rust-preventive coating composition according to any one of (1) to (4) above, wherein the content of the aqueous titanium chelate compound (C) is 0.1 to 4.5 parts by mass, calculated as TiO2, per 100 parts by mass of the zinc-based powder (B). (6) The anti-rust coating composition according to any one of the above (1) to (5), further comprising at least one component (A2) selected from alkoxysilanes, hydrolysates of alkoxysilanes, and hydrolyzed condensates of alkoxysilanes. (7) The anti-rust coating composition according to any one of the above (1) to (6), wherein the content of the zinc-based powder (B) is 80 mass % or less of the solid content of the anti-rust coating composition. (8) The rust-preventive coating composition according to any one of the above (1) to (7), having a pigment volume concentration (PVC) of 70% or more. (9) The anticorrosive coating composition according to any one of the above (1) to (8), which is a primary anticorrosive coating composition. (10) An anti-rust paint composition kit having a first agent and a second agent, wherein the first agent contains silica nanoparticles (A1), a water-based titanium chelate compound (C) and water, and the second agent contains at least one zinc-based powder (B) selected from zinc powder and zinc alloy powder. (11) The rust-preventive coating composition kit according to the above (10), wherein the first agent further contains at least one component (A2) selected from alkoxysilanes, hydrolysates of alkoxysilanes, and hydrolyzed condensates of alkoxysilanes. (12) An anti-rust coating film formed from the anti-rust coating composition according to any one of (1) to (8) above, or the anti-rust coating composition kit according to (10) or (11) above. (13) A primary rust-preventive coating film formed from the rust-preventive coating composition according to (9) above, or the rust-preventive coating composition kit according to (10) or (11) above. (14) A rust-preventive substrate comprising a substrate and the rust-preventive coating film according to (12) above formed on the substrate. (15) A rust-preventive substrate comprising a substrate and the primary rust-preventive coating film according to (13) above formed on the substrate. (16) A method for producing a rust-preventive substrate, comprising the steps of: [1] applying to a substrate the rust-preventive coating composition according to any one of (1) to (9) above, or a mixture obtained by mixing the first and second parts of the rust-preventive coating composition kit according to (10) or (11) above; and [2] curing the rust-preventive coating composition or the mixture applied to the substrate to form an anti-rust coating film on the substrate. EXAMPLES

[0118] The anti-rust coating composition of the present disclosure will be described in more detail below with reference to examples, but the anti-rust coating composition of the present disclosure is not limited to these examples.

[0119] The components used in the examples and comparative examples are as follows. Surface conditioner: "TEGO Twin 4000", Manufactured by Evonik Japan Co., Ltd., density 1.0g / cm 3 Water-based titanium chelate: "TYZOR TE" Manufactured by Dolph Ketal Corporation, USA. Triethanolamine titanium chelate, Solid concentration: 80% by mass, density: 1.06g / cm 3 , TiO2 equivalent: 13.69% by mass Water-based titanium chelate: "TYZOR LA" Manufactured by Dolph Ketal Corporation, USA. Ammonium Lactate Titanium Chelate, Solid concentration: 50% by mass, density: 1.21g / cm 3 , TiO2 equivalent: 13.6% by mass An aqueous silica sol containing silica nanoparticles (A1) and water: "Snowtex AK-YL", Nissan Chemical Co., Ltd., SiO2 content: 30.5% by mass, Solid content concentration 31.2% by mass, density 1.22g / cm 3, Average particle size 50~80nm, pH4.2, "Snowtex AK-L", Nissan Chemical Co., Ltd., SiO2 content: 20.5% by mass, Solid concentration 21.2% by mass, density 1.14g / cm 3 Average particle size 40~50nm, pH4.2 Inorganic / organic hybrid water-based binder containing silica nanoparticles (A1), alkoxysilane component (A2), water, crosslinker and curing catalyst: "Dynasylan SIVO 140", Manufactured by Evonik Japan Co., Ltd. SiO2 content 14.25% by mass, Solid content concentration 22.5% by mass, density 1.1g / cm 3 , pH 3.8 Conductive pigment: "3 types of zinc oxide", Manufactured by Hakusui Tech Co., Ltd., density 5.8g / cm 3 , zinc oxide Extender pigment: "Satintone W", BASF, density 2.6g / cm 3 , calcined kaolin Aluminum phosphate-based ingredient: "LF BOSEI PM-303W" Manufactured by Kikuchi Color Co., Ltd., density 3.0g / cm 3 , Aluminum dihydrogen tripolyphosphate (treated with molybdic acid) Zinc powder: "F-2000" Honjo Chemical Co., Ltd., density 7.1g / cm 3

[0120] [Preparation Example] Preparation of 1st and 2nd Agents Deionized water, surface conditioner, water-based titanium chelate compound, water-based silica sol and inorganic / organic hybrid water-based binder were charged into a container in the amounts (parts by weight) shown in Tables 1 to 4, and stirred at 25°C for 1 hour to prepare the first agent.

[0121] The conductive pigment, extender pigment, aluminum phosphate-based component, and zinc powder were mixed in the amounts (parts by mass) shown in Tables 1 to 4 to prepare a second agent.

[0122] [Examples 1 to 8, Comparative Examples 1 to 2] Preparation of anti-rust coating composition The first and second parts were charged in a polyethylene container in the ratios (parts by mass) shown in Tables 1 to 4, and dispersed for 5 minutes using a high-speed disperser to prepare anti-rust coating compositions.

[0123] [Creating test panels] Each of the anti-rust paint compositions obtained in the examples and comparative examples was applied to a structural steel plate (JIS G3101:2015, SS400, dimensions: 150mm x 70mm x 2.3mm, sandblasted) so that the dry film thickness was 15μm. Next, the applied composition was dried for 7 days in a constant temperature and humidity room at a temperature of 23°C and a relative humidity of 50% in accordance with the standard of JIS K5600-1-6:2016 to prepare a test plate with an anti-rust coating film formed on the structural steel plate. The dry film thickness was measured using an electromagnetic film thickness gauge "LE-370" (manufactured by Kett Electric Laboratory Co., Ltd.).

[0124] [White rust resistance] The two test plates were stacked in tap water and placed in a polyethylene bag (hereinafter also referred to as "PE bag"). Approximately 50 g of tap water was added to the PE bag in a paper cup, and the PE bag was closed with packing tape to obtain a test bag. The obtained test bag was left in a thermostatic chamber at 50°C for 7 days, after which the test plate was removed from the test bag and the surface was thoroughly dried. The condition of the mating surfaces of the test plates (the state of white rust development on the mating surfaces) was evaluated. The evaluation criteria for white rust are as follows:

[0125] AA: No white rust. BB: A small amount of white rust is observed. CC: White rust is observed, but not significantly widespread. DD: White rust is observed over the entire surface.

[0126] [Water resistance (red rust resistance)] The test panels were exposed outdoors for three days on a device that was kept horizontal and sprayed with tap water, with the painted surface constantly wet. According to the PINPOINT RUSTING standard of ASTM (American Society for Testing and Materials) standard D-610, the area ratio (%) of the test panel that had developed red rust (excluding 1 cm of each corner) was visually evaluated on a scale of 1 to 10.

[0127] [Evaluation criteria for rust condition (ASTM D610)] 10: No rust is observed, or the area ratio of rust is 0.01% or less. 9: The area ratio of rust is more than 0.01% and 0.03% or less. 8: The area ratio of rust is more than 0.03% and 0.1% or less. 7: The area ratio of rust is more than 0.1% and 0.3% or less. 6: The area ratio of rust is more than 0.3% and 1% or less. 5: The area ratio of rust is more than 1% and 3% or less. 4: The area ratio of rust is more than 3% and 10% or less. 3: The area ratio of rust is more than 10% and 16% or less. 2: The area ratio of rust is more than 16% and 33% or less. 1: The area ratio of rust is more than 33% and less than 50%. 0: The area ratio of rust is more than 50% and less than 100%.

[0128] [Storage stability] After preparation of the first agent, it was stored at 23°C for 2 days and 2 months. Using the first agent after storage, an anti-rust paint composition was prepared in the same manner as above. Using the obtained anti-rust paint composition, the above test plate was prepared in the same manner as above. The obtained test plate was subjected to the above water resistance (red rust resistance) test.

[0129] [Salt spray corrosion resistance] The test plate obtained in the above [Preparation of test plate] was placed in a spray cabinet at a temperature of 35°C ± 2°C in accordance with JIS K5600-7-1:2016, and an aqueous sodium chloride solution (concentration: 5%) was continuously sprayed onto the anti-rust coating film of the test plate. The state of rust of the anti-rust coating film 500, 1600, and 3600 hours after the start of spraying was evaluated in accordance with the above criteria of ASTM standard D-610 in the same manner as in the above water resistance (red rust resistance) test, and was evaluated on a scale of 10 to 10.

[0130] [Table 1]

[0131] [Table 2]

[0132] [Table 3]

[0133] [Table 4]

Claims

1. Silica nanoparticles (A1), At least one zinc-based powder (B) selected from zinc powder and zinc alloy powder; an aqueous titanium chelate compound (C); Water and Contains The content of the aqueous titanium chelate compound (C) is 0.1 to 2.0 parts by mass, calculated as TiO 2 , per 100 parts by mass of the zinc-based powder (B); Anti-corrosive paint composition.

2. The aqueous titanium chelate compound (C) has the formula: Ti(X) 4 2. The rust-preventive coating composition according to claim 1, wherein the compound is at least one selected from organotitanium compounds represented by the following formula (wherein X is each independently a hydroxy group, an alkoxy group or a chelating substituent, provided that at least one X is a chelating substituent) and oligomers thereof.

3. 3. The rust-preventive coating composition according to claim 2, wherein the aqueous titanium chelate compound (C) is an organic titanium compound in which the chelating substituent is a ligand derived from an alkanolamine, a ligand derived from a hydroxycarboxylic acid, or a ligand derived from a salt of a hydroxycarboxylic acid.

4. 4. The rust-preventive coating composition according to claim 3, wherein the aqueous titanium chelate compound (C) is an organic titanium compound in which the chelating substituent is a ligand derived from an alkanolamine.

5. 2. The anti-rust coating composition according to claim 1, further comprising at least one component (A2) selected from alkoxysilanes, hydrolysates of alkoxysilanes, and hydrolyzed condensates of alkoxysilanes.

6. 2. The anti-rust coating composition according to claim 1, wherein the content of the zinc-based powder (B) is 80 mass % or less of the solid content of the anti-rust coating composition.

7. 2. The rust-preventive coating composition according to claim 1, wherein the pigment volume concentration (PVC) is 70% or more.

8. The anti-rust coating composition according to claim 1, which is a primary anti-rust coating composition.

9. A rust-preventive paint composition kit having a first agent and a second agent, The first agent contains silica nanoparticles (A1), a water-based titanium chelate compound (C) and water, The second agent contains at least one zinc-based powder (B) selected from zinc powder and zinc alloy powder, The content of the aqueous titanium chelate compound (C) is 0.1 to 2.0 parts by mass, calculated as TiO 2 , per 100 parts by mass of the zinc-based powder (B); Anti-rust paint composition kit.

10. The rust-preventive coating composition kit according to claim 9, wherein the first agent further contains at least one component (A2) selected from an alkoxysilane, a hydrolyzate of an alkoxysilane, and a hydrolysis condensate of an alkoxysilane.

11. An anti-rust coating film formed from the anti-rust coating composition according to any one of claims 1 to 7, or the anti-rust coating composition kit according to claim 9 or 10.

12. A primary rust-preventive coating film formed from the rust-preventive coating composition according to claim 8 or the rust-preventive coating composition kit according to claim 9 or 10.

13. A rust-preventive substrate comprising a substrate and the rust-preventive coating film according to claim 11 formed on the substrate.

14. A rust-preventive substrate comprising a substrate and the primary rust-preventive coating film according to claim 12 formed on the substrate.

15. [1] A step of coating a substrate with a mixture obtained by mixing the anticorrosive coating composition according to any one of claims 1 to 8 or the first and second agents of the anticorrosive coating composition kit according to claim 9 or 10; [2] A step of curing the anti-rust paint composition or the mixture applied to the substrate to form an anti-rust coating film on the substrate; The method for producing a rust-preventive substrate comprising the steps of:

Citation Information

Patent Citations

  • Zinc-rich paint containing organic titanium chelate coupling agent and preparation method thereof

    CN104927540A

  • Pigment for corrosion preventive coating composition and corrosion preventive coating composition therewith

    JP2002053769A

  • paint composition

    JP2004501233A

  • Rust-preventive water-based coating composition containing no chromium

    JP2006028372A

  • Non-chromate aqueous surface treating agent for surface treatment of metallic material

    JP2007238976A